2018
DOI: 10.14238/pi58.2.2018.71-4
|View full text |Cite
|
Sign up to set email alerts
|

Hematological parameters and remission induction of childhood acute lymphoblastic leukemia

Abstract: Background High-risk acute lymphoblastic leukemia (ALL) is one of the most common childhood malignancies in Indonesia. Many factors can inhibit the induction of remission. Hematological parameters are usually not normal. Identification of corresponding factors is important to increase the likelihood of successful inductions.Objective To assess for associations between hematological parameters and induction of remission in children with acute lymphoblastic leukemia.Methods Data were collected from medical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…9,10 Male predominance was found in other studies as well. 11 Fever and pallor were more prevalent (Figure 1) than other studies. 12 This may be due to delayed diagnosis and referral causing advanced presentation.…”
Section: Discussionmentioning
confidence: 74%
“…9,10 Male predominance was found in other studies as well. 11 Fever and pallor were more prevalent (Figure 1) than other studies. 12 This may be due to delayed diagnosis and referral causing advanced presentation.…”
Section: Discussionmentioning
confidence: 74%
“…8 Complications from hyperleukocytosis such as hyperviscosity, and tumor lysis syndrome, may lead to bleeding, respiratory distress, and thromboembolism, thus increasing the risk of mortality. 6,9,10 We found that 84% of the high-risk status patients died, which was significantly higher than mortality in the standard-risk patients (57%). The mean survival times were 583.40 (70.75) days and 1,407.96 (139.81) days, respectively.…”
Section: Discussionmentioning
confidence: 74%
“…Rahim P, et al 20 found the incidence of remission as high as 100% in patients with Hb levels <5 g/dl. Study by Perdani RRW, et al 21 at Kariadi Hospital on 55 paediatric patients with ALL also did not show a significant relationship between Hb levels and remission, and remissions were more common in children with anaemia. The difference in prognosis based on Hb levels is thought to be because the lower Hb levels (Hb <8g /dl) are more frequently found in types of leukaemia with better outcomes (TEL/AML1, hyperdiploidy).…”
Section: Discussionmentioning
confidence: 84%
“…This study showed the remissions tended to occur in patients with platelet counts >30,000/cu mm and this was statistically significant. Perdani RRW, et al 21 performed a study on 55 patients with ALL showing that as many as 56% of patients had thrombocytopenia (<150,000/cu mm) and this was significantly associated with a lower remission rate than normal platelet levels or thrombocytosis. It can be seen that there are differences in the platelet cutoffs used in different studies, thus allowing for differences in results.…”
Section: Discussionmentioning
confidence: 99%